The recycling of domestic waste in the Cape Peninsula: implications for environmental education - Gobregts, Engela (Rhodes University, Faculty of Education, Department of Education, 1995)
This case study investigates domestic waste recycling schemes in the Cape Peninsula with special reference to educational aspects as a basis for developing educational resource materials. It explores the question: "In what way can projects for the recycling of domestic waste serve as a vehicle for environmental education?". The study employs the concept of education for the environment, following a socially critical approach with action-oriented and participatory dimensions. The research sample constituted interviewees and/or workshop participants from fourteen different municipalities, six recycling industries, one private waste contractor and the three most prominent voluntary organisations involved in recycling in the Cape Peninsula. A small-scale -interview survey was done to review existing recycling initiatives, combined with a case study of several small participatory initiatives towards educational resource development. The results were analysed qualitatively. The case study indicates that recycling initiatives have excellent potential for education for the environment. This potential was partially explored in this research by addressing key issues such as the role of local authorities in recycling of domestic waste, the short-term perspectives on the part of the local authorities, as well as the importance of and constraints on participation in recycling projects and in the research. Other issues discussed include the educational implications of personal (economic) benefits of recycling, the social development dimension of some recycling projects, the value of school children organising recycling projects, limited teacher participation in existing recycling projects, and the need for environmental education resource material. The major value of the project lies however in critical reflection on the research process. Recommendations regarding participatory resource development as an approach to socially critical environmental education are put forward to inform similar studies in the future and to elucidate the approach. Recommendations regarding the recycling of domestic waste in the Cape Peninsula are also made.
Keywords: Recycling (Waste, etc.) -- South Africa; Refuse and refuse disposal -- South Africa; Environmental education -- South Africa